Effectiveness of extracurricular futsal training using small-sided games in improving aerobic capacity (vo2max) of students. - Yunus, Annizar Gunawan; Hermawan, Irwan; Arifin, Z.; Kurniawati, Ani (Universitas Suryakancana, 2025)
Small-sided games (SSG) are one of the training methods used by coaches to stimulate the technical, tactical, and physical components of futsal players. This study aims to determine the effect of small-sided games (SSG) training with high-intensity interval training (HIIT) on improving VO2 Max among futsal extracurricular students at SMAN 15 Garut. The issue addressed in this study is the suboptimal endurance level of many students involved in the futsal extracurricular program. The research used an experimental method with a one-group pre-test and post-test design. The sample consisted of 20 students. VO2Max measurements were conducted using the Bleep Test, a standard method for assessing aerobic capacity. Before the training program commenced, all participants underwent the Bleep Test to obtain baseline VO2Max values (pretest). The small-sided games training program was implemented over 14 sessions, with training frequency set at three times a week. Data analysis involved normality, homogeneity, and t-test, yielding a significant value of (p = 0.000) < 0.05, indicating a significant increase in VO2 Max with an average post-test value of 39.720. These findings confirm that SSG training with HIIT can effectively improve cardiovascular endurance in high school futsal players. The high-intensity small-sided games training method had a significant effect on improving VO2Max in these students.